Synthesis, characterization, in silico, and in vitro biological screening of coordination compounds with 1, 2, 4-triazine based biocompatible ligands and selected 3d-metal ions. Issue 10 (October 2020) - Ammal P, Rugmini; Prasad, Anupama R.; Joseph, Abraham
Abstract: A bidentate Schiff base ligand, MHMMT, obtained from 1, 2, 4-triazine derivative and 4-hydroxy-3-methoxy benzaldehyde and its Fe(III), Co(II), Ni(II), Cu(II), and Zn(II) complexes were synthesised in ethanolic media and characterized by various analytical techniques like elemental analyses, magnetic susceptibility measurements, FTIR, UV-VIS, proton NMR, ESR, spectroscopic and thermogravimetric studies. Various geometries like a tetrahedral for Co(II) and Zn(II) complexes, an octahedral for Fe(III) and Ni(II) complexes, and square planar for Cu(II) complex has been assigned. For all metals complexes except Co(II), a 2:1 ligand to metal ratio is observed, while Co(II) complex has a 1:1 ratio. In accordance with the probable activity spectra of substances as obtained from PASS analysis, in vitro α-amylase inhibition studies by starch-iodine method for ligand and complexes except that of Fe(III) and anticancer screening against human breast cancer cell lines MCF-7 using MTT assay for Fe(III) complex were conducted. The tested compounds were found to be good α-amylase inhibitors, characteristically similar to most of the antidiabetic drugs. Among the compounds, Cu(II) complex exhibited the highest α-amylase inhibitory activity. Furthermore, ligand and complexes were also exposed to in vitro antimicrobial activities, drug-likeness, bioactivity score prediction by Molinspiration software. Molecular docking analysis of selected compounds on α-amylase and VEGFR-2 kinase were carried out for confirming the experimental observations. Abstract : Inorganic hemistry, MHMMT; α-amylase; Molecular Docking; Geometry.